Recruitment of the thigh muscles during sprint cycling by muscle functional magnetic resonance imaging - Akima, H.; Kinugasa, R.; Kuno, S. (International Journal of Sports Medicine, 2005)
The purpose of the present study was to investigate recruitment patterns of the thigh muscles during maximal sprint cycling by muscle functional magnetic resonance imaging (mfMRI). Twelve healthy men participated in this study and performed 2, 5, and 10 sets of 6-s supramaximal cycling with a load of 7.5 % of their body weight with 0.5 min of rest between the sets. Before and immediately after the exercise, T2-weighted MR images, i.e. mfMRI, of the right-thigh were taken to calculate T2 of eleven thigh muscles. Vastus lateralis, semitendinosus, and sartorius were the highest activated, i. e. had the greatest T2 change, among the quadriceps, hamstring, and adductors, respectively, compared with other muscles. Total power output during 2, 5, and 10 sets of sprint cycling was correlated with percent change in T2 in the quadriceps correlated (r2 = 0.507 to 0.696, p < 0.01), the hamstring (r2 = 0.162 to 0.335, p < 0.05 ~ 0.001), and the adductor muscles (r2 = 0.162 to 0.473, p < 0.05 ~ 0.0001). With use of stepwise regression analysis, total power output was significantly correlated with % change in T2 of the vastus medialis (VM) (p < 0.0001) and vastus intermedius (VI) (p < 0.05) (r2 = 0.698, p < 0.0001). We concluded that eleven thigh muscles were activated non-uniformly, and that the VM and VI play a key role during maximal sprint cycling.